Causes of delays in budget absorption as the development of good governance on deconcentration and co-administration task budget (A case study at the work unit of DKP-NTB Province) - Muhamad Ichsan Wadi; Rr. Titiek Herawati; L. Hamdani Husnan (STIE Perbanas Surabaya, 2016)
The objective of study is to determine the causes of delays in the absorption of De-concentration (Decon) and Co-administration Task (TP) budget at the level of Work Unit. In carrying out its function as an agent of the Ministry of Maritime Affairs and Fisheries (DKP). The Work Unit has developed operational plan, nevertheless it plan could not be followed up. Such condition surely has consequences on the budget absorption at the Work Unit. This study is a qualitative study using a case study approach. The study uses a holis-tic single case study. The results indicate that there are many obstacles encountered by the Work Unit in carrying out its daily activities related to budget absorption. The obstacles may be from internal factors and external factors. The strong intervention of principal in Decon and TP budget is a key issue of the external factor that makes the Work Unit unable to be consistent to the operational plan drawn up. Besides, the procurement of goods and services through the Procurement Services Unit is also an obstacle for the Work Unit in executing the work using tender mechanism. Other external factors are the mechanisms of Money Supply (UP) and the Change of Money Supply (GUP) that cause the Work Unit to get difficulty in setting up funds for activities. Meanwhile, the internal factors that con-strain the Work Unit are issues concerning Human Resources, Standard Operating Proce-dures and Performance Evaluation that have not been implemented well in the internal Work Unit. The theoretical implication of the study is the dominant intervention of the principal (central government) to the agent (Work Unit) is a resistance to the implementa-tion of the values of effectiveness and efficiency in the concept of good governance.